The favorable retroactivity in administrative law penalties - Baca Oneto, Víctor (2016)
An issue that has always caused controversy, both in the theory and in the practice, is the application of the law over time, which becomes more complex in terms of its non-retroactivity or retroactivity. In the present article, the author develops theretroactivity of the most favorable rule principle. First, the author describes the concept and fundamentals of retroactivity. Then, he reports its normative support and its delimitation. Finally, the author exposes the most discussed and controversial assumptions on its application and non-application, making parallels with its regulation in Spain.